Individual differences in political aggression: The role of social integration, perceived grievances and low self-control - Pauwels, Lieven (European journal of criminology, 2020)
Several models have been suggested for studying (self-reported) aggression. Less frequently, these theories are empirically applied to explain individual differences in political aggression. The present study examines the role of distal, intermediate and proximate mechanisms in a net-sample of 6020 young adults. Using log-linear structural equation modelling, the independent effects of cumulative social integration, perceived personal and group injustices and low self-control are assessed. It is assumed that these factors contribute to the ‘crystallization of discontent’ by fostering religious authoritarianism, political powerlessness, support for extremist beliefs and online exposure to extremist content. Support for extremist content and online exposure to extremist content are strong predictors, and function as different routes towards political aggression. The results support an integrated approach towards the study of political aggression. Implications for future studies are discussed.